Supporting women’s research in predominantly undergraduate institutions: Experiences with a National Science Foundation ADVANCE Institutional Transformation Award - Rabinowitz, Vita C.; Valian, Virginia (Frontiers in Psychology, 2022)
This paper describes the Gender Equity Project (GEP) at Hunter College of the City University of New York (CUNY), funded by the U. S. NSF ADVANCE Institutional Transformation Award (ITA) program. ADVANCE supports system-level strategies to promote gender equity in the social and natural sciences, but has supported very few teaching-intensive institutions. Hunter College is a teaching-intensive institution in which research productivity among faculty is highly valued and counts toward tenure and promotion. We created the GEP to address the particular challenges that faculty, especially White women and faculty of color, face in maintaining research programs and advancing in their careers at teaching-intensive institutions. During the course of the ADVANCE award, its centerpiece was the Sponsorship Program, a multifaceted paid mentorship/sponsorship program that paired each participant with a successful scholar in her discipline. It offered extensive professional development opportunities, including interactive workshops and internal grants to support research. The GEP helped change key policies and practices by ensuring that all faculty were treated fairly in areas like provision of research start-up funds and access to guidance on how to prepare for tenure and promotion. Qualitative and quantitative evidence suggests that participation in the Sponsorship Program boosted research productivity and advanced the careers of many of the women who participated; the Program was highly rated by all participants. Some of the policy and practice changes that the GEP helped bring about were sustained at Hunter beyond the award period and some were adopted and disseminated by the central office of CUNY. However, we were not able to sustain the relatively expensive (but cost-effective) Sponsorship Program. We share the lessons we learned, including that creating a diverse, successful social and natural scientific workforce requires sustained support of female faculty employed at teaching-intensive colleges. We acknowledge the difficulties of sustaining gains, and offer ideas about how to make the case for gender equity when women seem to be doing “well enough.” We underscore the imperative of building support for women’s research in teaching-intensive institutions, where most women scientists are employed, and well over 90% of all college students—a disproportionate percentage of whom are female, minoritized, or both—are educated.